Lipid Profile Alterations in the Metabolic Syndrome The Latest Biochemical and Physiological Aspect (Global Journal of Medical Research, 2015)
Cardiovascular and cerebrovacular complications form a major challenge in the management of the The Metabolic Syndrome. The risks of development are compounded by simultaneous occurrence of Type 2 diabetes mellitus (T2DM), dyslipid emias, hypertension and other medical conditions. The significant increase in morbidity, mortality along with premature death and disabilities resulting from these conditions in both developed and developing is a matter of great concern. The article makes a microanalysis of Biochemical alterations associated with dyslipidemias in cases of metabolic syndrome.
Keywords: apolipoproteins; esterfication; syndrome; circumference; waist; glucocorticoids; lipase